MR T2-relaxation time as an indirect measure of brain water content and disease activity in NMOSD. Issue 7 (28th April 2022) - Cacciaguerra, Laura; Pagani, Elisabetta; Radaelli, Marta; Mesaros, Sarlota; Martinelli, Vittorio; Ivanovic, Jovana; Drulovic, Jelena; Filippi, Massimo; Rocca, Maria A
Abstract : Objective: Since astrocytes at the blood–brain barrier are targeted by neuromyelitis optica spectrum disorder (NMOSD), this study aims to assess whether patients with NMOSD have a subclinical accumulation of brain water and if it differs according to disease activity. Methods: Seventy-seven aquaporin-4-positive patients with NMOSD and 105 healthy controls were enrolled at two European centres. Brain dual-echo turbo spin-echo MR images were evaluated and maps of T2 relaxation time (T2rt) in the normal-appearing white matter (NAWM), grey matter and basal ganglia were obtained. Patients with a clinical relapse within 1 month before or after MRI acquisition were defined 'active'. Differences between patients and controls were assessed using z-scores of T2rt obtained with age-adjusted and sex-adjusted linear models from each site. A stepwise binary logistic regression was run on clinical and MRI variables to identify independent predictors of disease activity. Results: Patients had increased T2rt in both white and grey matter structures (p range: 0.014 to <0.0001). Twenty patients with NMOSD were defined active. Despite similar clinical and MRI features, active patients had a significantly increased T2rt in the NAWM and grey matter compared with those clinically stable (p range: 0.010–0.002). The stepwise binary logistic regression selected the NAWM as independently associated with disease activity (beta=2.06, SE=0.58, Nagelkerke R 2 =0.46, p<0.001). Conclusions: In line with the research hypothesis, patients with NMOSD have increased brain T2rt. The magnitude of this alteration might be useful for identifying those patients with active disease.